PERLINDUNGAN HUKUM TERHADAP KONSUMEN USAHA RITEL MODERN DI INDONESIA (STUDI PENELITIAN DI WARUNG SAYUR SEGAR CANGAKAN KABUPATEN KARANGANYAR) - Flau Rita Nindya Astika; Supriyono, Supriyono; Fatma Ayu Jati Putri (Jurnal Cakrawala Ilmiah, 2025)
The rapid growth of modern retail in Indonesia, driven by urbanization, technological advancements, and changing consumer behavior, has disrupted the existence of traditional stalls and MSMEs. Modern retail offers advantages in efficiency, pricing, promotions, and convenience; however, its presence creates competitive imbalances that threaten local social and cultural values. This study analyzes the legal protection provided to consumers in the modern retail sector, particularly concerning halal product certification and the circulation of expired goods, through a case study at Warung Sayur Segar in Karanganyar Regency. The findings indicate that while most products are halal-certified and procedures for handling complaints about expired products are available, the effectiveness of their implementation remains low due to weak education, supervision, and legal awareness. Regulations such as Law No. 8 of 1999 and the Halal Product Assurance Law No. 33 of 2014 provide a solid legal framework but have not yet fully ensured optimal consumer protection. Therefore, enhanced public outreach, the application of supporting monitoring technologies, and synergy between the government, businesses, and consumer institutions are required to establish an inclusive and adaptive protection system aligned with the dynamics of modern retail.